Tactics of treatment of patients with acute coronary syndrome - G.T.Madjidova (Zien Journals, 2022)
Hypertrophic cardiomyopathy (GKM), according to the current classification [1], is classified as primary cardiomyopathies, primarily a genetically determined disease of the heart muscle characterized by a complex set of specific morphofunctional changes and a steadily worsening course. The symptoms of the disease are varied and vague and are associated with hemodynamic disturbances - diastolic dysfunction against the background of massive hypertrophy of the left (CH Q) and or right ventricular myocardium, often asymmetric due to thickening of the interventricular septum (IVS), left ventricle (CH Q) with frequent development of outflow tract obstruction, myocardial ischemia, pathology of autonomic circulation regulation and disruption of electrophysiological processes in the heart [2-4]. The prognosis in GCM is variable, so one of the main challenges is to differentiate the risk of fatal complications of the disease, to look for available prognostic prognosis and criteria for evaluating the effectiveness of treatment
Keywords: background; determined; interventricular; evaluating